Análisis bioético de la técnica de clonación híbrida terapéutica - García Neim, R. Enrique (2018)
This essay aims to study differently, the parts of the process of cloning technique Hybrid Therapeutics toreach critical Bioethics of the final product, the Cybris, which is an embryonic stem from hybrid originthat bioethics critics can be reprogrammed cell by physical or chemical means for use in human tissuetransplantation.